Deixis Analysis on Rafi Bastos’ Stand Up Comedy - Jeriko Nadeak; Muhammad Daniel Ramadhan; Muhammad Thoriq Mulya Akbar; Mia Perlina (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Research aims to analyze the use of deixis in Rafi Bastos’ stand-up comedy video titled “USA vs Brazil”. This study examines the types of deixis used, such as person, time, place, discourse, and social deixis according to Levinson’s theory. To collecting the data, this study using a descriptive qualitative method. The analysis shows that person and discourse deixis are the most frequently use types, reflecting a comedy style based on personal narrative and story context. This study provides the insight into the importance of deixis in pragmatic communication and how adjustments to cultural and social contexts can influence international comedy.